Embroidering Two Worlds: A Phenomenological Exploration of Working Wives Dual Roles in Balancing Career and Family - Satiti , Wening Sekar; Nurhayati , Siti Rohmah (Universitas Pendidikan Ganesha, 2025)
Harmony in living dual roles is a subjective phenomenon that must reflect personal perspectives. Therefore, exploring the perceptions of individuals who live this phase of life is essential to understand the nature of harmony in living dual roles and to recognize the results of harmony. This study uses a qualitative approach with a phenomenological method. The participant selection process uses a purposive sampling technique so that the number of participants is 5 participants. The data obtained are organized into categories, synthesized, and arranged into patterns that are then concluded from them so that they are easy to understand. The results of this study illustrate how work and family harmony can be achieved by working wives. There are two categorizations found in this study. The first categorization is the ways and aspects that help working wives achieve harmony. The second categorization is the emotions felt by working wives while living their dual roles. Working wives in their marriages have dual roles that are no longer a conflict or challenge or something surprising. They have found a rhythm on how to deal with every problem that arises by negotiating it with family members and coworkers and superiors. Stress is a form of normality that arises when there is intervention either from family to work or from work to family. However, commitment and priority help them in determining attitudes and reducing guilt when intervention and negotiation need to be done. Success in living a dual role is supported by negotiation skills, social support, and flexibility in roles. The implications of this study indicate the need for more family-friendly work policies and the importance of emotional support from the immediate environment to help working wives achieve a healthy life balance.